Poloxamer-based hydrogel with EGCG and rhEGF for diabetic foot ulcer treatment - Ahe Mo Se; Linwei Li; Mengting Yu (Journal of Materials Science: Materials in Medicine)
Abstract A thermosensitive hydrogel dressing was developed for the healing of diabetic foot ulcers (DFUs) using Epigallocatechin gallate (EGCG) and recombinant human epidermal growth factor (rhEGF). Hyaluronic acid (HA), poloxamer 407 (P407), and pectin (PE) were used to form the sol-gel transition matrix, which exhibited a sol-to-gel transition around 30 °C. The hydrogel was physiologically stable. Structural and morphological characterization using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) confirmed the efficient incorporation of EGCG and rhEGF in a porous nanoarchitecture. Rheological analysis showed the storage modulus is quite constant over the frequency range (0.01–10 Hz), and compression analysis showed a compressive strength of 40.85 kPa, ensuring mechanical appropriateness for various wound conditions. This hydrogel had a water content of 76.64% and a water vapor transmission rate of 6011.44 g/m2/day, favorable to maintain a moist wound surface. Antibacterial tests showed inhibition rates of 73.53% against Escherichia coli and 75.37% against Staphylococcus aureus. In vitro with RAW 264.7 macrophages and L929 fibroblasts showed >90% cell survival, increased migration with 92.53% wound closure by 48 h, strong antioxidant activity, and considerable decrease in TNF-α and IL-6 (pro-inflammatory cytokines). Combining a natural antioxidant and bioactive protein within a responsive hydrogel matrix presented a synergistic solution, holding significant promise for enhancing diabetic wound healing by antimicrobial, anti-inflammatory, and regenerative processes. Graphical Abstract The fabrication of the EGCG-rhEGF@HA-P407-PE hydrogel, an advanced wound dressing designed for diabetic foot ulcers